Hermeneutical and hermeneutical aesthetics of the image. The articulation of image and language in H. G. Gadamer and G. Boehm - Domínguez, Javier (Estudios de Filosofía, 1997)
This article exposes the meaning and aims of Hermeneutic Aesthetics, expressed in Gadamer's Philosophy, and those of Hermeneutics of image, represented by Boehm's Theory of Art. Though both proposals root in Contemporary Art and Philosophy, they suggest a new experience of the History of Art in its wider sense. Their main interest is to avoid the isolation of image from the spheres of comprehension with which we are acquainted, and to avoid as well the supplanting of artistic image by the rigid discursive language of interpretation.